Introduction to public health in pharmacy - Levin, Bruce Lubotsky; Hanson, Ardis; Hurd, Peter D. ([New York] : Oxford University Press, 2018)
'Introduction to Public Health in Pharmacy' takes an approach that is both global and local. Macro-level examinations of health care systems and funding mechanisms around the world and advice for culturally competent, client-centered communication regarding nutrition and proper self-administration of medications encapsulate pharmacists' dual roles as guardians of global public health and providers of personalized care. Written in accordance with the latest guidelines from the Center for the Advancement of Pharmacy Education, this text offers an accessible introduction for pharmacy students and a comprehensive refresher for pharmacists already in practice.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 1, 2018).
Keywords: Public health; Pharmacy